Strategi Pengembangan Higher Order Thinking Skills (HOTS) dalam Pembelajaran Matematika SD: Tinjauan Pustaka - Mailani, Elvi; Nur Rarastika; Devita Sari Purba; Sabaria Napitupulu; Jhon Daniel Anselino Malau (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
Mathematics learning at elementary school level plays an important role in forming higher order thinking skills (HOTS) from an early age. However, the implementation of HOTS at elementary school level still faces various challenges, such as conventional learning approaches and teachers' low understanding of effective strategies. This study aims to identify and analyze various learning strategies that can develop HOTS in the context of elementary school mathematics learning. This research was conducted through a literature review with a descriptive qualitative approach, using relevant scientific sources. The results of the study indicate that there are five main effective strategies, namely Problem-Based Learning (PBL), Project-Based Learning (PJBL), Contextual Teaching and Learning (CTL), Discovery Learning, and Inquiry-Based Learning (IBL). These strategies have been proven to improve students' critical, creative, reflective, and problem-solving thinking skills. Therefore, teachers need to be provided with ongoing training so that they are able to implement these strategies optimally in meaningful and adaptive mathematics learning.